Perceived Parental Acceptance and Cyberbullying Perpetration among Chinese Adolescents: Moderated Mediation Models of Materialism and Insecure Attachment - Geng, Jingyu (Journal of interpersonal violence, 2022)
Cyberbullying perpetration (CP) is a common and devastating network deviation behavior. Some parenting factors for CP have been identified, but few studies have examined the correlation between perceived maternal/paternal acceptance (PMA/PPA) and CP, and the mediating and moderating mechanisms underlying this relation are also largely unknown. Thus, by using a cross-sectional designed questionnaire survey of 4,206 adolescents (M = 16.41 years, SD = 0.77), the current study examined the relationship between PMA/PPA and CP, as well as the mediating effect of materialism and the moderating effects of father/mother?child attachment anxiety and attachment avoidance in this relation. The results showed that PMA/PPA was protective factors of CP. The moderated mediation models showed that materialism played a partial mediation role in the relationship between PMA/PPA and CP. Moreover, the direct association of PMA/PPA with CP was exacerbated by stronger father/mother?child attachment anxiety, in contrast, it was weakened by stronger father/mother?child attachment avoidance. Besides, both father/mother?child attachment anxiety and father/mother?child attachment avoidance strengthened the direct relationship between materialism and CP, and further strengthened the indirect association of PMA/PPA with CP. This study highlighted the importance of uncovering the link between perceived parental acceptance and adolescents? CP and emphasized the underlying mechanisms, which are of great significance for the prevention and intervention of adolescents? CP.